Overexpression of multivalent transcription factor, ctcf in hela cell lines - Nurul Wahida, Ab. Ghani (Universiti Sains Malaysia, 2008)
Transformation of pCI-CTCF plasmid was done after receiving this recombinant construct from Dr. Elena M. Klenova, Gene Regulation Laboratory, University of Essex, UK. The plasmid was propagated in E.coli DHS-a competence cell. Following transformation, a transformant containing the recombinant plasmid was selected and cultured overnight in LB Broth. The plasmid was then extracted using a plasmid extraction kit QIAprep Spin Miniprep Kit (QIAGEN, Germany). Purified plasmid was further analysed and characterized. The plasmid was then transfected into HeLa cells using Calcium Phosphate method. Following transfection, the HeLa cells were lysed and the supernatant of the lysed cells was analysed using Sodium Dodecyl Sulfate Polyacrylamide Gel Electrophoresis (SDS-PAGE) followed by Western Blotting using anti CTCF monoclonal antibody. There is a positive expression of exogenous CTCF detected in the lysate compare to the normal HeLa cell lines control. However due to short period of time for this project, transfection-efficiency was not properly estimated. This work established conventional, cheap and reasonable transfection method for future functional assay works in the lab.